Kerjasama Guru PAI dan Orang Tua dalam Meningkatkan Baca Tulis Al-Qur’an Siswa SMP Muhammadiyah 1 Medan - Muliadi Muliadi; Hafsah Hafsah; Zulkifli Nasution (CV. ALIM'SPUBLISHING, 2024)
Abstract. This study aims to evaluate the form of cooperation between PAI teachers and parents in improving the literacy of the Qur'an in the students of SMP Muhammadiyah 1 Medan, assess the level of literacy of students in the Qur'an, and analyze the supporting and inhibiting factors in the collaboration. The research method used is qualitative descriptive with a pedagogical approach. Data collection techniques include observation, interviews, documentation, and triangulation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing which aimed to clearly describe the process and results of cooperation between PAI teachers and parents. The results of the study show that: 1) The form of cooperation between PAI teachers and parents includes open communication, direct guidance, and the use of students' Qur'an reading and writing control books. 2) The ability to read and write the Qur'an of Muhammadiyah 1 Medan Junior High School students shows that some students still lack understanding and are not fluent in reading and writing the Qur'an in accordance with the rules of tajweed. 3) The supporting factor in the cooperation between PAI teachers and parents is active involvement in providing education to students. Meanwhile, the inhibiting factor is that not all parents can communicate effectively with PAI teachers, either directly or indirectly.